2014
DOI: 10.3126/aej.v15i0.19809
|View full text |Cite
|
Sign up to set email alerts
|

Performance of landrace and improved rice varieties under the system of rice intensification management in Bajhang District of Nepal

Abstract: Participatory action research was conducted in were, respectively, 24.5 vs. 11.3, 21.5 vs. 9.5, 305 vs. 273, 273.5 vs. 233.8, and 7.6 vs. 4.46

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In our second study, we observed no significant difference in yield between the improved dwarf variety Sukhadhan-3 and the heirloom, photoperiod-insensitive variety Tilkidhan. This result is consistent with a previous evaluation (Khadka, Acharya & Uphoff, 2014) in which, under SRI management, a two-fold increase in yield was observed from a locally-adopted rice variety known as Hansaraj Basmati in Bajang district of Nepal in the foothills of the Himalayas. Similarly, Ahmed, Dutta & Ray (2015) also found the traditional variety Koiya Boro under SRI management giving a 16% higher yield compared to that from currently recommended practices, and a 33% increase compared to traditional cultivation practices.…”
Section: Discussion Of Results Through Rank-ordering and Multiple Facsupporting
confidence: 92%
“…In our second study, we observed no significant difference in yield between the improved dwarf variety Sukhadhan-3 and the heirloom, photoperiod-insensitive variety Tilkidhan. This result is consistent with a previous evaluation (Khadka, Acharya & Uphoff, 2014) in which, under SRI management, a two-fold increase in yield was observed from a locally-adopted rice variety known as Hansaraj Basmati in Bajang district of Nepal in the foothills of the Himalayas. Similarly, Ahmed, Dutta & Ray (2015) also found the traditional variety Koiya Boro under SRI management giving a 16% higher yield compared to that from currently recommended practices, and a 33% increase compared to traditional cultivation practices.…”
Section: Discussion Of Results Through Rank-ordering and Multiple Facsupporting
confidence: 92%
“…Highest grain yield was observed in SRI (6.13 tonha -1 ) followed by traditional transplanting (5.82 tonha -1 ). Other researchers also reported highest grain yield for SRI (Duttarganvi et al, 2016;Tomar et al, 2018;Bhandari et al, 2020;Chen et al, 2013;Khadka et al, 2014). Lowest grain yield was observed in Wet DSR broadcasting (4.92tonha-1).…”
Section: Resultsmentioning
confidence: 79%
“…Effective tillers showed a higher percentage under the SRI method (87.9%) compared to conventional management (84.5%) (Khadka et al, 2014). The number of tillers per hill increased significantly at the 40 × 40 cm spacing at 30 DAT.…”
Section: Effects On Yield Attributesmentioning
confidence: 92%